Temporal analysis of the state of the Gbele Resource Reserve in the Upper West Region, Ghana - Aabeyir, Raymond; Peprah, Kenneth; Amponsah, Amos (Frontiers in Forests and Global Change, 2024)
This paper assessed the changes in the forest cover of the Gbele Resource Reserve from 1990 to 2020. This provides a basis for strengthening management decisions to protect the resources in the Gbele Resource Reserve effectively. Landsat images for 1990, 2000, 2010 and 2020 were obtained from the United States Geological Service site. They were processed and classified in the System for Earth Observation Data Access, Processing, & Analysis for Land Monitoring (SEPAL), a web-based cloud computing platform. The accuracy of the images was assessed using 50 ground-truth points obtained from the 3-5 meter spatial and near-daily temporal resolution planet satellite images from Norway's International Climate and Forest Initiative (NICFI). Post classification change detection was used to analyse the changes in land cover from 1990 to 2000, 2000 to 2010 and from 2010 to 2020. The analysis revealed that the total forest area was 55273.2 ha. In 1990, 74.9 % of the reserve was open forest and 24.6 % was shrubs/grass. The open forest declined to 65.8 % in 2000 and further to 62.4 % in 2010 while the shrubs/grass cover increased to 35.7 in 2010. As of 2020, the forest increased to 73.6 % while the shrub/grass cover declined to 25.8 %. These changes could be attributed partly to charcoal production which has been a livelihood in the fringe districts and the communities within the reserve. Rosewood logging for export which came to lamplight in the early 2000s could also partly explain the decline in the forest for the period. The sharp increase in the forest cover from 2010 to 2020 could also be due to the ban on the harvest and exportation of rosewood after 2010. The changes in the extent of the reserve from 1990 to 2020 indicate that the reserve is vulnerable to excessive exploitation and could also be resilient if deliberate efforts are made to protect it. It is recommended that the fringe district and municipal Assemblies should strengthen the enforcement of the ban on the logging of the rosewood and trees in the reserve for the production of charcoal.